Comparación de dos técnicas quirúrgicas escrotal y pre-escrotal en caninos. - Guaman Llanga, Katherine Isabel (Machala : Universidad Técnica de Machala, 2022)
The present work was carried out in the city of Machala, in the teaching clinic of Veterinary Specialties, of the Faculty of Agricultural Sciences, in the Technical University of Machala, located at kilometer 5 ½ via Pasaje, had as objective to compare the surgical process and between the scrotal and prescrotal castration technique in canines, evaluating both the surgery time (min) and the post-surgical recovery days (10 days). For this, we worked with 10 dogs, with average ages of 2 to 4 years, of which 5 were performed with the prescrotal approach technique (Treatment A) and the remaining 5 with the scrotal technique (Treatment B). The method used was descriptive, the statistical analysis was used Microsoft Excel where the results were graphed in bars; where the results obtained as the surgery time have the minimum time difference, as a result in the postoperative period greater inflammation and greater bleeding were observed in the scrotal technique, in the prescrotal technique it was observed that patients lick the incision area . Covering all these points, a conclusion was reached where the best castration technique was the pre-scrotal.
El presente trabajo fue realizado en la ciudad de Machala, en la clínica docente de Especialidades Veterinaria, de la facultad de Ciencias Agropecuarias, en la Universidad Técnica de Machala, ubicada en el kilómetro 5 ½ vía Pasaje, tuvo como objetivo comparar el proceso quirúrgico y post quirúrgico entre la técnica de castración escrotal y pre-escrotal en caninos, evaluando tanto el tiempo de cirugía (min), como días de recuperación post quirúrgico (10 días). Para ello se trabajo con 10 perros, con edades promedio de 2 a 4 años, de los cuales 5 se realizó con la técnica de abordaje pre escrotal (Tratamiento A) y los restantes 5 con la técnica escrotal (Tratamiento B). El método utilizado fue descriptivo, el análisis estadístico se utilizo Microsoft Excel en donde se realizó grafica de los resultados en barras; en donde los resultados obtenidos como el tiempo de cirugía tienen la minina diferencia de tiempo, como resultado en el post quirúrgico se observó mayor inflamación y mayor sangrado en la técnica escrotal, en la técnica pre escrotal se observo que los pacientes se lamen la zona de incisión. Abarcando todos estos puntos se llegó a una conclusión en donde la mejor técnica de castración fue la pre escrotal.
Keywords: ESCROTAL; PRE ESCROTAL; CIRUGIA